Household and household-related waste generation and characteristics in rural areas: A case study in Tanjungsari Sub-district - Jussac Maulana Masjhoer; Syafrudin Syafrudin; Maryono Maryono (Center for Science and Technology, IAIN Surakarta, 2022)
Waste management issues in rural locations differ from those in metropolitan ones. Unmanaged waste has the potential to harm the rural environment. Understanding the generation and characteristics of household and household-related waste is the starting point for planning waste management. Accurate measurement of waste generation and characteristics helps optimize waste reduction and recycling efforts. Therefore, this study aims to measure the waste generation and characteristics in rural areas using the Indonesia National Standard 19-3964-1994 method. The survey team visited 60 samples of residential and non-residential properties in the Tanjungsari Sub-district for eight consecutive days. Based on the results, the waste generation was 0.34 kg person-1 day-1. Organic waste (food waste, leaves, paper, and wood) accounts for the majority of garbage (81,34%), followed by inorganic materials (plastic, fabric, other materials, metal, and glass) at 15.66%, 1.86%, 0.91%, 0.12%, 0.11% respectively. The residential waste density is 196.1 kg m-3, while in non-residential areas is 63.63 kg m-3. Family size and income, living habits, and the type of economy or industry that develops have influenced the rural waste generation and composition. Rural waste management strategies need to consider organic waste as a raw material in composting or fermentation.